Biomimicry Learning as Inspiration for Product Design Innovation in Industrial Revolution 4.0 - Dina Lestari (IJCAS (International Journal of Creative and Arts Studies), 2020)
ABSTRACTNature can be a source of unlimited inspiration, biomimicry is an innovative approach to find sustainable solutions to overcome problems and meet human needs by imitating existing patterns and strategies in nature. The Industrial Revolution 4.0 brought many changes in human life, changes in lifestyles, ways of working, ways of learning, and ways of communicating between humans in many aspects. Most University students make use of technology to find and develop their ideas especially in creative industries where the OIM (Observe, Imitate, Modify) practice can be done through the Internet by observing from another researcher's observation. While biomimicry offers researchers to observe nature and create technology innovation inspired by nature. Students need to experience and learn from nature and use technology wisely. This study examines the biomimicryinspired works of Product Design undergraduate program students of Podomoro University Jakarta. The methodology research that we use in this study is a qualitative participatory method with comparative and correlational studies. The content of this study is to learn and evaluate the process and result of student's biomimicry observation into innovative product design. The conclusion can also be drawn that comparing the different levels of students which is the first year, second year, and third-year students by using the biomimicry observation approach will show variated concepts and skills on their work depending on what knowledge that they have learned from each semester. Pembelajaran Biomimikri sebagai Inspirasi dalam Inovasi Desain Produk di Era Revolusi Industri 4.0 ABSTRAK Alam dapat menjadi sumber inspirasi tanpa batas, biomimikri adalah pendekatan inovatif untuk menemukan solusi berkelanjutan untuk mengatasi berbagai permasalahan dan memenuhi kebutuhan manusia dengan meniru pola serta strategi yang nyata di alam. Revolusi Industri 4.0 membawa banyak perubahan dalam kehidupan manusia, perubahan gaya hidup, cara bekerja, cara belajar, dan cara berkomunikasi antara manusia dalam banyak aspek. Sebagian besar mahasiswa memanfaatkan teknologi untuk menemukan dan mengembangkan ideide mereka terutama di industri kreatif di mana praktik ATM (Amati, Tiru, Modifikasi) dapat dilakukan melalui Internet dengan mengamati dari pengamatan peneliti lain. Sementara biomimikri menawarkan peneliti untuk mengamati alam dan menciptakan inovasi teknologi yang terinspirasi oleh alam. Diharapkan dengan riset ini siswa bisa mendapatkan pengalaman nyata, mereka dapat termotivasi untuk mempelajari alam dan juga dapat menggunakan teknologi secara bijaksana. Riset ini bertujuan untuk mengkaji karya-karya yang terinspirasi biomimikri dari mahasiswa program sarjana jurusan Desain Produk Universitas Agung Podomoro Jakarta. Metodologi penelitian yang digunakan dalam riset ini adalah metode kualitatif parsitipatif dengan pendekatan korelatif serta komparatif. Konten kajian dalam studi ini merupakan evaluasi serta proses pembelajaran mahasiswa dalam penciptaan desain produk inovatif. Dari hasil riset ini dapat ditarik kesimpulan bahwa ternyata setelah melakukan perbandingan rancangan mahasiswa tahun pertama, kedua dan ketiga dengan menggunakan pendekatan observasi biomimikri maka ditemukan adanya perbedaan hasil serta tingkat keterampilan pada masing-masing angkatan tergantung dari pengetahuan yang mereka telah pelajari dan dapatkan di setiap semesternya.